From supervisory control to PLC code: a way to speed-up Constructive/Virtual Commissioning of Manufacturing Systems. Issue 4 (2020) - Basile, F.; Ferrara, L.
Abstract: This paper demonstrates that it is nowadays possible to successfully adopt a virtual/constructive approach in the contest of automated manufacturing systems. The design and the implementation of the control software is usually not considered a crucial step in the development cycle of these systems but it plays a key role to reduce time and costs of the real commissioning. In this paper, recent computer technology progress, some results from discrete event systems research and a proposed software are exploited to show that a virtual/constructive approach can effectively speed-up the design and the implementation of the control software.